Spinal Accessory Nerve: Ultrasound Findings and Correlations with Neck Lymph Node Levels - Hong, M. J.; Baek, J. H.; Kim, D. Y.; Ha, E. J.; Choi, W. J.; Choi, Y. J.; Lee, J. H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
Purpose: To evaluate the ultrasound characteristics of the spinal accessory nerve (SAN) and correlate nerve location with neck lymph node level.Materials and Methods: 50 participants with 100 SANs were enrolled in this study. The SAN was traced from the trapezius muscle to the upper neck and was identified by a hypoechoic linear structure without color Doppler flow. The ultrasound characteristics of the SAN, such as visibility, diameter, relationship with adjacent structures, and its correlation with lymph node levels, were evaluated.Results: The SAN was identified in 96 %-100 % of segments. The mean diameter of the SAN was 0.54 ± 0.09 mm. The SANs was located between the trapezius and levator scapulae muscles and 90.8 % were traced into the trapezius muscle. In the upper neck, the SAN passed deep into the sternocleidomastoid (SCM) muscle in 38 % of cases and between the two heads of the SCM muscle in 62 % of cases. The SAN was found at neck lymph node levels II, III, IV, and V, but not I or VI.Conclusion: Continuous ultrasound monitoring of the SAN and its correlation with lymph node levels is possible in most patients. Our current findings may assist in the future prevention of SAN injury during ultrasound-guided procedures.
Keywords: ultrasound; anatomy; thyroid